2013
DOI: 10.4314/ajtcam.v10i5.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fractionated extracts and isolated pure compounds of spondias mombin (<i>L. Anacardiaceae</i>) leaves on novelty-induced rearing and grooming behaviors in mice.

Abstract: This study attempted to elucidate the neurotransmitter systems involved in the neurophysiological properties of ethanolic extract, fractions and pure isolates of Spondias mombin leaves in mice (n = 6) after intraperitoneal (i.p.) route of administration.The crude ethanolic extract of spondian mombin leaves was fractionated using the partitioning method to obtain the ethylacetate, butanolic and aqueous fractions. Open column chromatographic fractionation of the ethylacetate fraction yielded seven sub-fractions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Ethanol extract of M. indica peel has been investigated and reported to inhibit α-amylase and α-glucosidase activities, and to ameliorate diabetes related biochemical parameters in streptozotocin (STZ)-induced diabetic rats [ 20 ]. Previous studies have reported extraction of different chemical compounds such as phenolic acid 6-alkenyl-salicylic acid, anarcardic acid, chlorogenic acid, ellagic acid, betulin, coumaroyl, quercetin, and gallic acid from S. mombin , which exhibited different biological activities including antidiabetic, anti-inflammatory and anti-oxidant effects [ 15 , 21 , 22 , 23 , 24 ]. On the other hand, studies have reported that bioactive compounds identified from M. indica leaves include quercetin and chlorogenic acid which possess anti-oxidant, anti-inflammatory, and antidiabetic activities [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol extract of M. indica peel has been investigated and reported to inhibit α-amylase and α-glucosidase activities, and to ameliorate diabetes related biochemical parameters in streptozotocin (STZ)-induced diabetic rats [ 20 ]. Previous studies have reported extraction of different chemical compounds such as phenolic acid 6-alkenyl-salicylic acid, anarcardic acid, chlorogenic acid, ellagic acid, betulin, coumaroyl, quercetin, and gallic acid from S. mombin , which exhibited different biological activities including antidiabetic, anti-inflammatory and anti-oxidant effects [ 15 , 21 , 22 , 23 , 24 ]. On the other hand, studies have reported that bioactive compounds identified from M. indica leaves include quercetin and chlorogenic acid which possess anti-oxidant, anti-inflammatory, and antidiabetic activities [ 25 ].…”
Section: Introductionmentioning
confidence: 99%